If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x * ln(x) + x = 0 Multiply x * ln 2lnx * x + x = 0 Multiply lnx * x 2lnx2 + x = 0 Solving 2lnx2 + x = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1x' to each side of the equation. 2lnx2 + x + -1x = 0 + -1x Combine like terms: x + -1x = 0 2lnx2 + 0 = 0 + -1x 2lnx2 = 0 + -1x Remove the zero: 2lnx2 = -1x Divide each side by '2nx2'. l = -0.5n-1x-1 Simplifying l = -0.5n-1x-1
| 1.39x=8.34 | | -5(4+m)+2= | | m-3.75=12.25 | | lnx+ln(x+2)=-1 | | 15x^2-21=0 | | 8x=7-3y9y=-20x+13 | | 15s+22=7m+18 | | (9w-x)(9w-x)= | | w-18=14 | | x^2+2x+e=0 | | 6(8)-2(b)=50 | | (7v-4w)(7v-4w)= | | 2(8)+b=25 | | -3=9x-2 | | 6(5)-2(b)=50 | | 81=36+6x | | 22x-9-16x+4=18x-7-12x+14 | | 2(5)+b=25 | | 49=3w+10 | | -2-5x=2x+12 | | x^2-x-t-5= | | -4x+6+2(x-5)=-2(x+4) | | (3a-3)(a+5)= | | 4y+9-2=0 | | 38.79+4x=110 | | X^2+14x-63=0 | | 4+2x=5x+7-4x | | 2(4y^2-11y+8)=0 | | 2x-4x=9+8x | | 3x-x^2=2 | | y=(2x+5)(x-1) | | 5x+.75x=850 |